Understanding John Austin's Legal Positivism Theory and Hans Kelsen's Pure Legal Theory: an Introduction for Beginners - Ahmad Fanani; Muhammad Sulthon Zulkarnain (Pustaka Peradaban, 2022)
John Austin and Hans Kelsen are widely recognized as influential legal experts. Their theories and thoughts about law are still a reference for jurists around the world. John Austin's Legal Positivism Theory offers a scientific and measurable legal paradigm when most existing legal products do not have certainty and are not measurable with certainty. Meanwhile, Hans Kelsen's Pure Law theory was also born as a form of response to various legal products at that time which could not be separated from various social, political, and cultural interests. So that law as a product of the state does not have authoritative legal certainty. The thoughts of both have sparked various responses and many among legal experts around the world. Therefore this article will further explore the two thoughts of these two figures in the hope of helping to show that Pure Law Theory and positive law theory are still relevant to contemporary legal theory.